Contribution of IDO to human respiratory syncytial virus infection. Issue 4 (15th May 2019) - Benavente, Felipe M; Soto, Jorge A; Pizarro-Ortega, Magdalena S; Bohmwald, Karen; González, Pablo A; Bueno, Susan M; Kalergis, Alexis M
Abstract: IDO is an enzyme that participates in the degradation of tryptophan (Trp), which is an essential amino acid necessary for vital cellular processes. The degradation of Trp and the metabolites generated by the enzymatic activity of IDO can have immunomodulating effects, notably over T cells, which are particularly sensitive to the absence of Trp and leads to the inhibition of T cell activation, cell death, and the suppression of T cell effector functions. Noteworthy, T cells participate in the cellular immune response against the human respiratory syncytial virus (hRSV) and are essential for viral clearance, as well as the total recovery of the host. Furthermore, inadequate or non-optimal polarization of T cells is often seen during the acute phase of the disease caused by this pathogen. Here, we discuss the capacity of hRSV to exploit the immunosuppressive features of IDO to reduce T cell function, thus acquiring relevant aspects during the biology of the virus. Additionally, we review studies on the influence of IDO over T cell activation and its relationship with hRSV infection. Graphical Abstract: Review of the capacity of hRSV to exploit the immunosuppressive features of IDO to reduce T cell function and activation.